Comparison between invasive and noninvasive techniques of evaluation of microvascular structural alterations. Issue 5 (May 2018) - De Ciuceis, Carolina; Agabiti Rosei, Claudia; Caletti, Stefano; Trapletti, Valentina; Coschignano, Maria A.; Tiberio, Guido A.M.; Duse, Sarah; Docchio, Franco; Pasinetti, Simone; Zambonardi, Federica; Semeraro, Francesco; Porteri, Enzo; et al.
Abstract : Background: The evaluation of the morphological characteristics of small resistance arteries in humans is challenging. The gold standard method is generally considered to be the measurement by wire or pressure micromyography of the media-to-lumen ratio of subcutaneous small vessels obtained by local biopsies. However, noninvasive techniques for the evaluation of retinal arterioles were recently proposed; in particular, two approaches, scanning laser Doppler flowmetry (SLDF) and adaptive optics, seem to provide useful information; both of them provide an estimation of the wall-to-lumen ratio (WLR) of retinal arterioles. Moreover, a noninvasive measurement of basal and total capillary density may be obtained by videomicroscopy/capillaroscopy. No direct comparison of these three noninvasive techniques in the same population was previously performed; in particular, adaptive optics was never validated against micromyography. Methods: In the current study, we enrolled 41 controls and patients: 12 normotensive lean controls, 12 essential hypertensive lean patients, nine normotensive obese patients and eight hypertensive obese patients undergoing elective surgery. All patients underwent a biopsy of subcutaneous fat during surgery. Subcutaneous small resistance artery structure was assessed by wire micromyography and the media-to-lumen ratio was calculated. WLR of retinal arterioles was obtained by SLDF and adaptive optics. Functional (basal) and structural (total) microvascular density was evaluated by capillaroscopy before and after venous congestion. Results and conclusion: Our data suggest that adaptive optics has a substantial advantage over SLDF in terms of evaluation of microvascular morphology, as WLR measured with adaptive optics is more closely correlated with the M/L of subcutaneous small arteries ( r  = 0.84, P  < 0.001 vs. r  = 0.52, P  < 0.05, slopes of the relations: P  < 0.01 adaptive optics vs. SLDF). In addition, the reproducibility of the evaluation of the WLR with adaptive optics is far better, as compared with SLDF, as intraobserver and interobserver variation coefficients are clearly smaller. This may be important in terms of clinical evaluation of microvascular morphology in a clinical setting, as micromyography has substantial limitations in its clinical application due to the local invasiveness of the procedure.